The impact of routine surveillance screening with magnetic resonance imaging (MRI) to detect tumour recurrence in children with central nervous system (CNS) tumours: protocol for a systematic review and meta-analysis. Issue 1 (December 2016) - Main, Caroline; Stevens, Simon; Bailey, Simon; Phillips, Robert; Pizer, Barry; Wheatley, Keith; Kearns, Pamela; English, Martin; Wilne, Sophie; Wilson, Jayne
Abstract Background The aim of this study is to assess the impact of routine MRI surveillance to detect tumour recurrence in children with no new neurological signs or symptoms compared with alternative follow-up practices, including periodic clinical and physical examinations and the use of non-routine imaging upon presentation with disease signs or symptoms. Methods Standard systematic review methods aimed at minimising bias will be employed for study identification, selection and data extraction. Ten electronic databases have been searched, and further citation searching and reference checking will be employed. Randomised and non-randomised controlled trials assessing the impact of routine surveillance MRI to detect tumour recurrence in children with no new neurological signs or symptoms compared to alternative follow-up schedules including imaging upon presentation with disease signs or symptoms will be included. The primary outcome is time to change in therapeutic intervention. Secondary outcomes include overall survival, surrogate survival outcomes, response rates, diagnostic yield per set of images, adverse events, quality of survival and validated measures of family psychological functioning and anxiety. Two reviewers will independently screen and select studies for inclusion. Quality assessment will be undertaken using the Cochrane Collaboration's tools for assessing risk of bias. Where possible, data will be summarised using combined estimates of effect for time to treatment change, survival outcomes and response rates using assumption-free methods. Further sub-group analyses and meta-regression models will be specified and undertaken to explore potential sources of heterogeneity between studies within each tumour type if necessary. Discussion Assessment of the impact of surveillance imaging in children with CNS tumours is methodologically complex. The evidence base is likely to be heterogeneous in terms of imaging protocols, definitions of radiological response and diagnostic accuracy of tumour recurrence due to changes in imaging technology over time. Furthermore, the delineation of tumour recurrence from either pseudo-progression or radiation necrosis after radiotherapy is potentially problematic and linked to the timing of follow-up assessments. However, given the current routine practice of MRI surveillance in the follow-up of children with CNS tumours in the UK and the resource implications, it is important to evaluate the cost-benefit profile of this practice. Systematic review registration PROSPEROCRD42016036802